Panama Canal drought and supply chain disruptions in Asia-United States trade: Evidence from micro-level trade shipments and vessel trajectory data - Paul H. Jung; Kijin Kim; Ah-Hyun Jo; Joseph Seong-Hyun Cho (Asian Development Bank (ADB), 2025)
Global chokepoints such as the Panama Canal propagate drought shocks into supply chains, yet disruptions to shipments remain poorly investigated. We examine the impact of supply chain disruptions induced by the 2022-2023 Panama Canal drought on Asia-United States (US) trade flows. We fuse Automatic Identification System vessel trajectories with US Customs Bills-of-Lading, matching 95% of 29.6 million 2022-2023 filings to 48 million hourly vessel positions. Difference-in-differences and event study analysis results present that canal voyages of containerized shipments took 133.8 hours longer, spent 33.6 hours more stopped, and sailed 2.3 kilometers per hour slower, with route distance unchanged, and these disruptions more than reversed normal-time efficiency gains. Shipment times for metallic raw materials and light manufacturing shipments increased markedly, and there was no significant effect on food products. The results provide a robust foundation for valuing delay-induced opportunity costs and designing resilient trade-facilitation policies for export-oriented economies in Asia.
Keywords: 330; Panama Canal drought; maritime chokepoints; global supply-chain disruptions; Asia-US container trade; transaction-level trade data